2014
DOI: 10.1136/bmjopen-2013-004086
|View full text |Cite
|
Sign up to set email alerts
|

Does neonatal pain management in intensive care units differ between night and day? An observational study

Abstract: ObjectiveTo determine whether analgesic use for painful procedures performed in neonates in the neonatal intensive care unit (NICU) differs during nights and days and during each of the 6 h period of the day.DesignConducted as part of the prospective observational Epidemiology of Painful Procedures in Neonates study which was designed to collect in real time and around-the-clock bedside data on all painful or stressful procedures.Setting13 NICUs and paediatric intensive care units in the Paris Region, France.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 24 publications
3
17
0
2
Order By: Relevance
“…32 The reasoning for this approach was the improvements in infant pain management resulted by parental involvement. 1,4,5 Nurses in this study also identified the positive connection between learning to parent and parental involvement in pain management. 1,3 These subjective experiences further validate the earlier quantitative findings.…”
Section: Discussionmentioning
confidence: 72%
“…32 The reasoning for this approach was the improvements in infant pain management resulted by parental involvement. 1,4,5 Nurses in this study also identified the positive connection between learning to parent and parental involvement in pain management. 1,3 These subjective experiences further validate the earlier quantitative findings.…”
Section: Discussionmentioning
confidence: 72%
“…We were unable to determine the impact of pain management practices on prevalence estimates due to inadequate reporting. Because previous studies have noted variability in pain management practices between NICUs, and within the same NICU, unit and hospital based differences in pain management practices may have contributed to the variable prevalence estimates in this review.…”
Section: Discussionmentioning
confidence: 99%
“…This is a move towards neonate centred care within the highly technological environment of the NICU and the move is to have reliable pain control at all times [43].…”
Section: Pain Managementmentioning
confidence: 99%